What Factors Affect the Competiveness of Power Generation Sector in China? An Analysis Based on Game Cross-efficiency - Bai-Chen Xie; Jie Gao; Shuang Zhang; ZhongXiang Zhang (Fondazione Eni Enrico Mattei (FEEM), 2017)
China's unbundling reform in 2002 aimed to introduce competitiveness into the power industry, especially the generation sector, to improve its operational efficiency. Meanwhile, great concern about a range of environmental problems and global climate change increasingly calls for saving energy and abating emissions. Thus, the ability to balance the reduction of carbon emissions with economic benefits may to a great extent determine the competitiveness of power generation sector. This study first adopts the game cross-efficiency approach to evaluate the environmental efficiency of the generation sectors in China's 30 provinces. It then employs a system generalized method of moments model to explore the determinants of their performance while eliminating the associated endogeneity problem. The results of this first study combining the two methods indicate that efficiency gaps do exist among the regions even though overall efficiency has been improved. Despite the negative correlation between environmental efficiency and the thermal power ratio, the power mix should be adjusted gradually. The average firm size and capacity utilization rates are positive factors boosting the environmental efficiency. The incentive policies for clean energy development should be differentiated across regions according to their power mix and self-sufficiency ratio.
Keywords: Q54; Q55; Q58; Q43; Q48; O13; O44; R11; 330; Game Cross-efficiency; Data Envelopment Analysis; Generalized Method of Moments; Power Industry; Environmental Efficiency; China